The January 30, 1989 Arctic polar stratospheric clouds (PSC) event - Evidence for a mechanism of dehydration - Gandrud, B. W.; Dye, J. E.; Baumgardner, D.; Ferry, G. V.; Loewenstein, M.; Chan, K. R.; Sanford, L.; Gary, B. (1990)
In-situ particle measurements made aboard the NASA ER-2 in the Arctic on 890130 (YYMMDD) show Type 1 PSC particles over much of the flight, with instances of embedded Type 2 PSCs. The Type 2 particles were observed at temperatures warmer than the local frost-point temperature of water; extended up to the upper size cutoff of the instrument (about 24-micron diameter); and are shown to contain too large a volume to be primarily NAT. Based on measured vertical temperature profiles, it is concluded that the Type 2 particles observed on this day were formed above the aircraft in a region where saturation with respect to ice was achieved and were sufficiently large to have fallen into the path of the ER-2. Although the amount of material in the particles, expressed as water, is small by comparison to the total (vapor + aerosol) water concentration, the flux of water from the falling particles is of sufficient magnitude, if sustained, to lead to dehydration of the source region. These observations verify the mechanism for dehydration of polar vortex air masses by precipitation of ice particles.